Randomized, Double‐Blind, Placebo‐Controlled Trial of Intraarticular Trans‐Capsaicin for Pain Associated With Osteoarthritis of the Knee. Issue 9 (17th July 2019) - Stevens, Randall M.; Ervin, John; Nezzer, Jennifer; Nieves, Yeni; Guedes, Kimberly; Burges, Robin; Hanson, Peter D.; Campbell, James N.
Abstract : Objective: To assess the efficacy and safety of high‐purity synthetic trans‐capsaicin (CNTX‐4975) in patients with chronic moderate‐to‐severe osteoarthritis (OA)–associated knee pain. Methods: In this phase II multicenter double‐blind study, patients ages 45–80 years who had stable knee OA were randomized in a 2:1:2 ratio to receive a single intraarticular injection of placebo, CNTX‐4975 0.5 mg, or CNTX‐4975 1.0 mg. The primary efficacy end point was area under the curve (AUC) for change from baseline in daily Western Ontario and McMaster Universities Osteoarthritis Index pain with walking score (range 0–10, 0 = none and 10 = extreme) through week 12. Secondary efficacy end points included a similar AUC analysis of outcomes in patients treated with CNTX‐4975 0.5 mg, and evaluations extending to 24 weeks. Results: Efficacy was evaluated in 172 patients (placebo group, n = 69; CNTX‐4975 0.5 mg group, n = 33; CNTX‐4975 1.0 mg group, n = 70). At week 12, greater decreases in the AUC for the pain score were observed with CNTX‐4975 in the 0.5 mg and 1.0 mg groups versus placebo (0.5 mg group least squares mean difference [LSMD] −0.79, P = 0.0740; 1.0 mg group LSMD −1.6, P < 0.0001). Significant improvements were maintained at week 24 in the 1.0 mg group (LSMD −1.4, P = 0.0002). Treatment‐emergent adverse events were similar in the placebo and CNTX‐4975 1.0 mg groups. Conclusion: In this study, CNTX‐4975 provided dose‐dependent improvement in knee OA–associated pain. CNTX‐4975 1.0 mg produced a significant decrease in OA knee pain through 24 weeks; CNTX‐4975 0.5 mg significantly improved pain at 12 weeks, but the effect was not evident at 24 weeks.